Assessing the Photovoltaic Quality of Vacuum‐Thermal Evaporated Organic Semiconductor Blends. Issue 22 (19th December 2021) - Kaienburg, Pascal; Jungbluth, Anna; Habib, Irfan; Kesava, Sameer Vajjala; Nyman, Mathias; Riede, Moritz K.
Abstract: Vacuum‐thermal evaporation (VTE) is a highly relevant fabrication route for organic solar cells (OSCs), especially on an industrial scale as proven by the commercialization of organic light emitting diode‐based displays. While OSC performance is reported for a range of VTE‐deposited molecules, a comprehensive assessment of donor:acceptor blend properties with respect to their photovoltaic performance is scarce. Here, the organic thin films and solar cells of three select systems are fabricated and ellipsometry, external quantum efficiency with high dynamic range, as well as OTRACE are measured to quantify absorption, voltage losses, and charge carrier mobility. These parameters are key to explain OSC performance and will help to rationalize the performance of other material systems reported in literature as the authors' methodology is applicable beyond VTE systems. Furthermore, it can help to judge the prospects of new molecules in general. The authors find large differences in the measured values and find that today's VTE OSCs can reach high extinction coefficients, but only moderate mobility and voltage loss compared to their solution‐processed counterparts. What needs to be improved for VTE OSCs is outlined to again catch up with their solution‐processed counterparts in terms of power conversion efficiency. Abstract : The state‐of‐the‐art vacuum thermal‐evaporated organic solar cells (VTE OSCs) in their photovoltaic material quality is assessed. The comprehensive optoelectronic characterization yields four key metrics governing OSC performance—a new methodology that equally applies to solution‐processed OSCs. The five studied material blends give a representative overview of today's VTE OSCs and needs for improvement are identified for this industrially leading OSC technology.